Differential micronucleus frequency in isogenic human cells deficient in DNA repair pathways is a valuable indicator for evaluating genotoxic agents and their genotoxic mechanisms. (15th May 2018) - Saha, Liton Kumar; Kim, Sujin; Kang, Habyeong; Akter, Salma; Choi, Kyungho; Sakuma, Tetsushi; Yamamoto, Takashi; Sasanuma, Hiroyuki; Hirota, Kouji; Nakamura, Jun; Honma, Masamitsu; Takeda, Shunichi; et al.
Abstract : The micronucleus (MN) test has become an attractive tool both for evaluating the genotoxicity of test chemicals because of its ability to detect clastogenic and aneugenic events and for its convenience. As the MN assay has been mostly performed using only DNA repair‐proficient mammalian cells, we believed that the comparison of the MN frequency between DNA repair‐proficient and ‐deficient human cells may be an excellent indicator for detecting the genotoxic potential of test chemicals and for understanding their mode of action. To address this issue, the following five genes encoding DNA‐damage‐response (DDR) factors were disrupted in the TK6 B cell line, a human cell line widely used for the MN test: FANCD2, DNA polymerase ζ ( REV3 ), XRCC1, RAD54, and/or LIG4 . Using these isogenic TK6 cell lines, the MN test was conducted for four widely‐used DNA‐damaging agents: methyl methanesulfonate (MMS), hydrogen peroxide (H2 O2 ), γ‐rays, and mitomycin C (MMC). The frequency of micronuclei in the double strand break repair‐deficient RAD54 −/− /LIG4 −/− cells after exposure to γ‐rays, H2 O2, MMS and MMC was 6.2‐7.5 times higher than that of parental wild‐type TK6 cells. The percentages of cells exhibiting micronuclei in the base excision repair‐ and single strand break repair‐deficient XRCC1 −/− cells after exposure to H2 O2, MMC and MMS were all ∼5 times higher than those of wild‐type cells. In summary, a supplementary MN assay using the combination of RAD54 −/− /LIG4 −/−, XRCC1 −/− and wild‐type TK6 cells is a promising method for detecting the genotoxic potential of test chemicals and their mode of action. Environ. Mol. Mutagen., 2018. © 2018 Wiley Periodicals, Inc.